Exploring the Mediating Role of Self-Confidence in the Relationship Between Psychological Factors and Performance in China’s Tourism and Hotel Industry - Yunqian Du; Wenchu Huang; Yuge Li; Minghe Zhou; Dongshu Cheng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
As a whole, Chinese players fail to perform at their full potential due to psychological factors, which include psychological limitations that prevent them from performing at their maximum potential. This research aims to investigate the effect of psychological factors on a player's performance, with particular emphasis on the mediation effect of self-confidence as a factor affecting the player's performance. The purpose of this study necessitated the use of a quantitative research method, which was chosen because of its objective. As a result of the greater population of the study, the present study selected a quantitative research method as opposed to qualitative or mixed research methods in order to generalize the results. As a result of selecting a research method, a questionnaire was created and then divided into two sections in order to meet the requirements. A questionnaire based on demographic questions was used for the first part of the assessment. A second element of the questionnaire that is related to key variables is that there are twenty questions on it. Based on a questionnaire that is based on a Likert Scale of 1, 1 being Strongly Agreed, and 5 being Strongly Disagreed, the purpose of the study was measured through the use of Likert Scales. It was a quantitative approach that was used to obtain the study results. It was found that a total of 600 badminton players were surveyed in this study. Based on the primary data, a partial least squares (PLS) analysis was performed on the data. It has been shown that self-confidence stands as a mediator between psychological factors such as anxiety, punctuality, Tourist Comfort, and Victim, which have an effect on players' performance. The degree of punctuality and performance of players is moderated by the level of service provided by the hotel. As a result of the current study, Chinese players could be able to improve their performance. Furthermore, the current study may also be helpful to the Chinese sports industry and tourism industry in order to enhance the performance of their players in the future.